Keanekaragaman dan Kerapatan Jenis Mangrove di Desa Kase Kecamatan Leksula Kabupaten Buru Selatan - Efraim Samson; Vergenia Sigmarlatu; Deli Wakano (University of Halu Oleo, 2020)
This study aims to determine the diversity and density of mangrove vegetation in Kase Village, Leksula Subdistrict, South Buru Regency. The study uses the line transect method with several observation plots that are stratified. A total of 20 transects were placed at the study site with the size of each plot, namely for seedling level, which is 2 x 2 m, while for the level of a sapling, namely 5 x 5 m and for the level of trees, which is 10 x 10 m. The results showed that in the mangrove area in Kase Village, Leksula Subdistrict, South Buru Regency, 3 mangrove species were found, namely Rhizophora apiculata, Bruguiera gymnorhiza, and Sonneratia alba, which belong to two families (Rhizophoraceae, Sonneratiaceae) and 3 genera, (Rhizophora, Bruguiera, Sonneratia). The total number of mangrove individuals, that is 699 individuals from 419 levels of seedlings, 116 levels of a sapling, and 164 levels of trees. The species with the highest density and relative density values at the level of tree growth, namely Rhizophora apiculata, and at the level of sapling and seedlings, namely Bruguiera gymnorhiza. While Sonneratia alba, tends to have density values and species densities that tend to be low at all three growth rates. Furthermore, the results of the diversity index analysis in the mangrove area of Kase Village, Leksula Subdistrict, South Buru Regency, showed that the diversity of species (H´) mangroves for each growth level was 0.76 (seedlings); 0.82 (sapling); and 1.02 (trees), or classified as low to moderate category. Keywords: Mangrove, Diversity, Abundance, Kase Village Abstrak Penelitian ini bertujuan untuk mengetahui keanekaragaman dan kerapatan jenis vegetasi mangrove di Desa Kase, Kecamatan Leksula Kabupaten Buru Selatan. Penelitian menggunakan metode line transect dengan beberapa plot pengamatan yang dibuat bertingkat. Sebanyak 20 transek ditempatkan pada lokasi penelitian dengan ukuran plot masing-masing, yakni untuk tingkat semai, yakni 2 x 2 m, sedangkan untuk tingkat anakan, yakni 5 x 5 m dan untuk tingkat pohon, yakni 10 x 10 m. Hasil penelitian menunjukkan bahwa pada area mangrove di Desa Kase Kecamatan Leksula Kabupaten Buru Selatan, ditemukan 3 spesies mangrove yakni Rhizophora apiculata, Bruguiera gymnorhiza, dan Sonneratia alba, yang tergolong ke dalam dua family (Rhizophoraceae, Sonneratiaceae) dan 3 genus, (Rhizophora, Bruguiera, Sonneratia). Jumlah total individu mangrove, yakni 699 individu yang terdiri dari 419 tingkat semai, 116 tingkat anakan, dan 164 tingkat pohon. Spesies dengan nilai kerapatan dan kerapatan relatif tertinggi pada tingkat pertumbuhan pohon, yakni Rhizophora apiculata, dan pada tingkat anakan serta semai, yakni Bruguiera gymnorhiza. Sedangkan Sonneratia alba, cenderung memiliki nilai kerapatan dan kerapatan jenis yang cenderung rendah pada ketiga tingkat pertumbuhan tersebut. Kemudian, hasil analisis indeks keanekaragaman di area mangrove Desa Kase Kecamatan Leksula Kabupaten Buru Selatan, menunjukan bahwa keanekaragaman jenis (H´) mangrove untuk masing-masing tingkat pertumbuhan, yakni 0.76 (semai); 0.82 (anakan); dan 1.02 (pohon), atau tergolong kategori rendah hingga sedang. Kata Kunci: Mangrove, Keanekaragaman, Kerapatan, Desa Kase